Pengembangan E-LKPD Berbasis Model Project Based Learning (PJBL) Menggunakan Makanan Khas Bengkulu untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika pada Materi Pembulatan Bilangan Kelas IV Sekolah Dasar - Novia Kurnia Sari; Agus Susanta; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar, 2024)
This research aims to produce an E-worksheet product based on the Project Based Learning (PJBL) model using traditional Bengkulu food to improve the ability to solve mathematical problems in class rounding material. IV elementary school. This research is a Research and Development study (R&D with the ADDIE model. The subjects in this research were students of SDN 52 Bengkulu City, totaling 26 students in class IV B as the control class, and 26 students in class IV C as the experimental class. The instruments used in this research is an interview guide, questionnaire, and problem solving test in the form of essay questions via pretest and posttest. The data analysis technique in this research is validation analysis using Aiken's V and Interrater Reliability, teacher and student responses, as well as quantitative analysis using the t test. From the research results It is known that the results of material, language and design validation, as well as teacher and student responses to E-worksheets are very feasible and good for use in learning so that students are happy and interested in learning. The results of the effectiveness of E-worksheets are effective in influencing students' mathematical problems. Judging from the results of the scores The significance is 0.00, which is smaller than α = 0.05. Based on the gain-score test from using the E-worksheet, it gives a moderate gain score of 53%. So the mathematical problem solving abilities of students who use PjBL-based E-worksheets with typical Bengkulu food ingredients are higher than students who only use textbook worksheets from school so they are declared effective.